2011
DOI: 10.1145/2070781.2024224
|View full text |Cite
|
Sign up to set email alerts
|

Multi-perspective stereoscopy from light fields

Abstract: Figure 1: We propose a framework for flexible stereoscopic disparity manipulation and content post-production. Our method computes multi-perspective stereoscopic output images from a 3D light field that satisfy arbitrary prescribed disparity constraints. We achieve this by computing piecewise continuous cuts (shown in red) through the light field that enable per-pixel disparity control. In this particular example we employed gradient domain processing to emphasize the depth of the airplane while suppressing di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…The adaptation of stereoscopic content to a disparity range that provides a comfortable viewing experience has motivated a number of recent works that focus on disparity retargeting [Lang et al 2010;Kim et al 2011;Masia et al 2013;Kellnhofer et al 2013]. …”
Section: Stereoscopic Retargetingmentioning
confidence: 99%
“…The adaptation of stereoscopic content to a disparity range that provides a comfortable viewing experience has motivated a number of recent works that focus on disparity retargeting [Lang et al 2010;Kim et al 2011;Masia et al 2013;Kellnhofer et al 2013]. …”
Section: Stereoscopic Retargetingmentioning
confidence: 99%
“…It has been shown that given the simultaneous multiple views, LFs enable improved image analysis, e.g., stereo reconstruction [20], refocusing [29], saliency detection [23], and scene classification [39].…”
Section: Introductionmentioning
confidence: 99%
“…Extending this method to remap full-parallax light field content would introduce artifacts because of the increased number of views. Kim et al [10] extend the approach by proposing a framework for the generation of stereoscopic image pairs with per-pixel control over disparity, based on multi-perspective imaging from light fields. While their method might be extended to multi-view images, the associated optimization problem is too costly to be solved in a run-time setting.…”
Section: Related Workmentioning
confidence: 99%